(untitled) (Revista Rupturas, 2024)
This article analyzes the phenomenon of inequality in the distribution of wealth from a psychosocial perspective, emphasizing the individualist-collectivist cultural dimension. In the first theoretical part, it begins by describing some contributions of the social psychology perspective on inequality in the distribution of economic resources. In a second part, it reviews several recent scientific studies on the relationship between cultural individualism-collectivism and economic inequality. Finally, it presents the conclusions and limitations of the work, and proposes future lines of research.